Helicobacter pylori: past, current and future treatment strategies with gastroretentive drug delivery systems - Verma, Anurag; Dubey, Juhi; Hegde, Rahul Rama; Rastogi, Vaibhav; Pandit, J. K. (Journal of drug targeting, 2016)
Helicobacter pylori have been subject to intense investigation since its discovery from gastric biopsy in 1982. This gastropathogen has been regarded as serious public health problem due to its association with dyspepsia, gastritis, gastroduodenal ulcers, mucus-associated lymphoid tissue lymphoma and gastric carcinoma. In vivo eradication of established H. pylori infections is difficult due to several factors such as gastric niche, coccoid form due to sub-minimum inhibitory concentration of antimicrobials, bacterial load, primary antibiotic resistance, patient compliance and stability of therapeutics in gastric acid secretion. Considering these factors, a logical way to improve the outcome of the treatment is to develop dosage forms which are able to deliver the anti-helicobacter agents in the gastric niche for both local and systemic actions, simultaneously taking care of stability of therapeutics in acidic environment. Such dosage forms, which are popularly known as gastro retentive drug delivery systems (GRDDS), have the immense potential to effectively counter the problem of high bacterial load; prevent induction of coccoid bacteria thereby improving treatment outcome and compliance. This review describes efficacy of various therapeutic agents, treatment strategies and status of different GRDDS until now.